(untitled) (Kairaranga, 2024)
Ngā mihi ki a koe and to all of the viewers and readers of Kairaranga, it’s such a pleasure to have the chance to kōrero with you all today. Ko wai au? I te taha o tōku matua, no Indonesia ahau. I te taha o tōku māmā, no Airani, Kōtirana, me Ingarangi ahau. On my dad’s side, I’m from Indonesia, from Central Java, and from my mum’s side, Irish, Scottish, and English ancestry. I grew up in the beautiful west of Tāmaki Makaurau, amongst the kererū and kauri trees there, and that’s a place that has really shaped me. I did my schooling in Tāmaki Makaurau, out west in Auckland and then went to university in Tāmaki Makaurau and then offshore in the Netherlands. My career has basically been dedicated to children’s rights, human rights and social justice. Throughout the various roles that I’ve had, a focus on children and their rights has always been there, and over the past 10 years or so I’ve really deepened that even more. I went and did my Masters and then my PhD in international children’s rights law, but practice and working to advance the rights of tamariki, of mokopuna has always been something that has been my guiding force, whether that’s been overseas internationally working for organisations like Unicef advocating in places like the European Union and the Council of Europe, or back home here in Aotearoa New Zealand. I really have a strong belief in the potentiality of all of our mokopuna, all our children and young people. To see them fully flourish, their full range of holistic rights really need to be upheld and realised in their everyday lives. I guess it’s all of those different threads that have led me through into this role as Chief Children’s Commissioner, which is such a privilege, but also a very, very big responsibility. I’m grateful to work with an amazing team and board alongside me, and the focus is really now on ensuring that we’re advocating as strongly as possible for the rights of mokopuna here in Aotearoa New Zealand.